In the halls of history: the making and unmaking of the life-casts at the ethnography galleries of the Iziko South African Museum - Cedras, Robyn-Leigh (African Studies, 2017)
This mini-dissertation is a study of the phenomenon of life-casting and the display of these in the museum space. It looks specifically at the practice as it came into use at the turn of the twentieth century at the South African Museum in the Western Cape. The research aims to place the practice in context with the historical triggers and larger perspectives of the subject of indigenous races. A focus on particular life-casts and its display in designed productions allows the reader insight into knowledge production. I point to this to unpack a loaded history informing deeply seated identity constructs and prejudices. A trajectory of the use of the life-casts is supported by visual records included in this text. The museum's archive also affords a plethora of correspondence and research giving context and insight. A close analysis of the archive exposes the museum's processes and the exchange in consumption and production by museum visitors and related institutions both private and state supported. The making and unmaking of the life-casts acts as proxy for peoples brutally subjugated.